Application value of ultrasonic contrast imaging and ultrasonic parameters in post-transplant renal surgery - Liu, Xinwei; Liu, Dikuan; Long, Meizhen; Chen, Feng (Frontiers in Medicine, 2024)
Objective Utilize VUEBOX quantitative analysis software to perform quantitative analysis dynamic ultrasound contrast images of post-transplant renal patients were assessed quantitatively five parameters of ultrasonic contrast and two-dimensional ultrasound are examined to explore their six value in Diagnosing Renal Graft Dysfunction. Methods A retrospective analysis was conducted on 73 post-transplant renal patients who underwent ultrasound contrast examinations at Yiyang Central Hospital from July 2022 to December 2023, They were diagnosed clinically and pathologically. Based on pathological and clinical diagnostic results, the patients were divided into three groups: 47 cases in the stable renal function group, 18 cases in the acute rejection (AR) group, and 8 cases in the delayed graft function (DGF) group. All patients underwent routine ultrasound and ultrasound contrast examinations post-transplantation. By comprehensively assessing renal function test results, clinical course, and pathological findings, differences in ultrasonic contrast quantitative parameters were analyzed. Additionally, ROC curves were constructed to evaluate the diagnostic efficacy of ultrasound contrast in discriminating between transplant renal rejection reactions and delayed renal function recovery. Results Statistically significant differences in characteristics, such as renal segmental artery resistance index, were observed among the stable renal function group, AR group, and DGF group (all P < 0.05), while peak systolic velocity showed no statistical significance (P > 0.05). Differences in cortical time to peak (TTP), medullary time to peak(TTP), main renal artery rise time (RT), main renal artery(TTP), and main renal artery fall time (FT) were statistically significant among the stable renal function group, AR group, and DGF group (P < 0.05). ROC curve analysis demonstrated that the accuracy of quantitative parameters for the DGF group and AR group was as follows: Renal artery TTP = Renal artery RT > Renal artery FT > Medulla TTP > Cortex TTP (with respective area under the curve values of 0.828, 0.828, 0.758, 0.742, 0.719). Among these, Renal artery TTP and Renal artery RT exhibited larger AUC values, with sensitivities of 87.5% each and specificities of 81.2 and 87.5%, respectively. Conclusion There are discernible differences in VUEBOX quantitative parameters between post-transplant AR and DGF cases, thereby providing imaging references for diagnosing of acute rejection and functional impairment following renal transplantation.